Pengaruh Rekrutmen, Penempatan Kerja, dan Etos Kerja Terhadap Kinerja Karyawan PT Remiten Indonesia di Kuta, Bali - Suwandewi, Ayu Ditha; Ngurah Gede Sadiartha, A A; Suasti Puja, I Made (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
This study aims to determine the effect of recruitment, job placement, and work ethic on the performance of employees of PT Remiten Indonesia in Kuta Bali. The population and sample in this study were all employees of PT Remiten Indonesia in Kuta Bali, totaling 37 people determined by census techniques. The analytical technique used was multiple linear regression analysis. Based on the results of the analysis it was found that recruitment had a positive and partially significant effect on the performance of employees of PT Remiten Indonesia in Kuta Bali, work placement had a positive and partially significant effect on the performance of employees of PT Remiten Indonesia in Kuta Bali, work ethic had a positive and partially significant effect on performance of employees of PT Remiten Indonesia in Kuta Bali. Simultaneously recruitment, work placement and work ethic have a positive and significant effect on the performance of employees of PT Remiten Indonesia in Kuta Bali. The researcher suggests that the leadership of PT Remiten Indonesia in Kuta Bali pay attention to employee recruitment methods, be able to adjust knowledge and work so that they are able to act and behave well at work, do work sincerely and wholeheartedly and can do a good job. For future researchers to add other variables that have the potential to affect employee performance.